Differential expression and effect analysis of lncRNA-mRNA in congenital pseudarthrosis of the tibia - Li, Zhuoyang; Mei, Haibo; Liu, Kun; Yang, Ge (Frontiers in Genetics, 2023)
Background: To analyze the lncRNA-mRNA differential expression and co-expression network of periosteal stem cells (PSCs) from congenital pseudarthrosis of the tibia (CPT) and normal patients, and to explore the role of key lncRNAs. Methods: Differentially expressed lncRNAs and mRNAs in PSCs were obtained by sequencing, and biological functions of differentially expressed mRNAs were detected by gene ontology (GO), Kyoto encyclopedia of genes and genomes (KEGG) pathway and protein -protein interaction (PPI) analysis. The co-expression network of lncRNA-mRNA was constructed by correlation analysis of differentially expressed lncRNAs and mRNAs, and the key lncRNAs were screened according to the connectivity degree. After that, the cis-regulated target genes of differential expressed lncRNAs and mRNAs were predicted. Results: A total of 194 differentially expressed lncRNAs were identified, including 73 up-regulated and 121 down-regulated genes. A total of 822 differentially expressed mRNAs were identified, including 311 up-regulated and 511 down-regulated genes. GO, KEGG and PPI enrichment analysis showed that the regulatory function of differentially expressed mRNAs were mainly gathered in skeletal system development and tissue morphogenesis. The co-expression network with 226 nodes and 3390 edges was constructed based on correlation analysis. A total of 10 key lncRNAs, including FAM227B, POM121L9P, AF165147 and AC103702, were screened according to connectivity degree. Prediction of target genes indicated that FAM227B-FGF7 and AC103702-HOXB4/5/6 may play an important role in the pathogenesis of CPT. Conclusions: A total of 10 key lncRNAs, including FAM227B, POM121L9P, AF165147 and AC103702, occupy the core position in the co-expression network, suggesting that these lncRNAs and their target genes may play an important role in the pathogenesis of CPT.